Marxist Perspective In “Caged Bird” By Maya Angelou - I Made Satria Bayu Temaja; Novita Mulyana; I Nyoman Tri Ediwan; Gek Wulan Novi Utami (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Literature and social life have a close relationship. Many writers express ambiguous emotions when observing their surroundings. Society is a mixture of the upper and lower classes. Due to the imbalance of wealth, the lower classes often experience different fates in life, while the upper classes enjoy the benefits. Karl Marx has pointed out this social injustice in his theory. This research is an attempts to find elements of Marxism related to social inequalities in the poem